FAKTOR-FAKTOR YANG MEMPENGARUHI MAHASISWA AKUNTANSI DALAM PEMILIHAN KARIR SEBAGAI AKUNTAN PUBLIK DAN NON AKUNTAN PUBLIK (Studi Empiris pada Mahasiswa S-1 Akuntansi di Fakultas Ekonomi dan Bisnis Universitas Syiah Kuala) - Ag, Arman (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The purpose of this research is to examine the influence of financial reward, profesional training, social values, labor market consideration, and pride on the career selection as public accounting and non public accounting. Population of this research is 159 accounting students on semester 8 at Economics and Business Faculty Syiah Kuala University. Using simple random sampling, 61 students were chosen to be samples of the reserarchThe research type used in this research is hypothesis testing research. Type of data used is primary data. The data was collected by using questionnaire. The questionnaire were delivered to every students as sample. The analytical method used is logistic regression analysis with SPSS version 23.0.The result of the research shows that financial reward, profesional training, social values, labor market consideration, and pride simultaniously influence on the career selection as public accounting and non public accounting. Partially, profesional training influence on the career selection as public accounting and non public accounting. While financial reward, social values, labor market consideration, and pride had no influence on the career selection as public accounting and non public accounting.Keywords: career selection, public accounting and non public accounting profession, financial reward, profesional training, social values, labor market consideration, and pride.